CHANGES IN VITAMIN D IN OVERWINTERERS IN ANTARCTICA - M. Steinach; J. Tiedemann; E. Kohlberg; O. Opatz; A. Stahn; H. C. Gunga; M.A. Maggioni (2014)
Introduction Humans living and working in Antarctica face several physical and psychological demands such as very low temperatures, altered circadian rhythm, lengthy periods of complete darkness (PCD) from may to august, isolation and psychosocial stress. We assessed changes in Vitamin D concentration in overwinterers who inhabited the German Research Station Neumayer III (RSN3) for 13 months from 2007 to 2012 and evaluated these changes for dependency on month (M), season (S), gender (G), periodicity (P), fat mass (FM) and initial Vitamin D concentrations (IVDC). We hypothesized the existence of dependency of VD from these parameters during the overwinterers’ long-term stay in Antarctica. Material & Methods 25-OH-Vitamin D concentrations (VDC) were determined from venous blood samples of n=43 inhabitants of the RSN3 (28 male, 15 female) once per month, as were their FM using a scale and the bioimpedance-analysis. Resulting data were statistically analyzed using respective statistical software for dependency on M, S, G, P, FM and IVDC, as well as between VDC and IVDC after categorization in sufficient (SU), insufficient (IN) and deficient (DE) IVDC. Results The evaluation revealed a decrease in VDC during PCD with dependency from M (p<0.001) and S (p<0.001), but not from G (p=0.78). 49% of the participants had a VDC below 30nmol/l during PCD. A fitted sine curve described the P of VDC (p<0.0001, r=0.492, r2=0.242). IVDC exhibited a positive relationship with FM (n.sig. p=0.129, r=0.300, r2=0.09). VDC during PCD exhibited a positive relationship with IVDC (sig. P<0.001, r=0.533, r2=0.284). There also was a dependency from IVDC categorized for SU, IN and DE of VDC during PCD (p<0.01) and VDC post PCD (p<0.01). Discussion & Conclusions Long terms stays of humans in the antarctic German Research Station Neumayer III are associated with a considerable decrease in 25-OH-Vitamin D concentrations; these changes follow a periodicity. We found no dependency from gender. Our analysis revealed the ...